DAUR AL-MUDARRIS AL-NATHIQ BI AL-'ARABIYAH FI TARQIYAH AL-KIFAYAH AL-ITHISHALIYAH LADA AL-THULLAB AL-AJANIB - Atna Akhiryani (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
The study was aimed to figure out the role of Arabic native lecturers in improving student's communicative competences. It was quantitative research with descriptive analysis approach. The objects were students and Arabic native lecturers at Islamic and Arabic Sciences Institute Jakarta. The result of the research shows that improving student's communicative competences could be obtained by various factors such as lesson plans, language environment, etc. An Arabic native lecturer would not play a significant role in improving student's communicative competences unless other important factors well prepared. There were some problems found when the students was taught by native lecturers like the speed of speech of native lecturers, understanding an explanation of vocabulary, Arabic local dialects, and Arabic 'amiyah which was used occasionally by native lecturers. Therefore, Arabic native lecturers were suggested to be capable in contrasting both Arabic and Indonesian languages, understanding Indonesian cultures, using Arabic fushah, and avoiding using Arabic local dialects.DOI : 10.15408/a.v3i1.2888